1999
DOI: 10.1007/s11926-999-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-induced inflammatio and cartilage degradation

Abstract: In the past year, there have been advances in our understanding of the induction of cartilage damage by calcium-containing crystals. Mechanisms of deposition and the biologic effects of crystals have been further characterized, as has the interaction between crystals and leukocytes. Studies of the clinical diagnosis of crystal deposition diseases suggest that accuracy with microscopy needs to be enhanced. Normal values for serum NTPPPHase have been established and optimal diagnostic imaging strategies for calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…BCP crystals would be ideal targets for anti-OA therapy, since the acute symptoms of OA diseases are readily treated medically while the chronic effects of crystals are not. There are no effective drugs on the market to date which can inhibit the deposition or cause reabsorption of calcium-containing crystals 50…”
Section: Osteoarthritis and Bcp Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCP crystals would be ideal targets for anti-OA therapy, since the acute symptoms of OA diseases are readily treated medically while the chronic effects of crystals are not. There are no effective drugs on the market to date which can inhibit the deposition or cause reabsorption of calcium-containing crystals 50…”
Section: Osteoarthritis and Bcp Crystalsmentioning
confidence: 99%
“…There are no effective drugs on the market to date which can inhibit the deposition or cause reabsorption of calcium-containing crystals. 50 Some promising pre-clinical results for OA treatment were recently submitted by Cheung et al 51 They reported that blocking the deposition of calcium-containing crystals by a new synthesised formulation of phosphocitrate can reduce cartilage degeneration in an animal model of OA. Treatment with the calcium crystal inhibitor reduced meniscal calcification and arrested OA progression.…”
Section: Osteoarthritis and Bcp Crystalsmentioning
confidence: 99%
“…14 The synovia of these joints are often inflamed; 15 the significance of this is a matter of great controversy. Wear debris, 16 crystals 17 or inflammatory cytokines [18][19][20] may cause synovitis in OA. Histological examination of the cartilage confirms the gross anatomy, and reveals a striking loss of proteoglycan from the matrix.…”
Section: Clinical Presentation and Pathophysiology Of Human Oamentioning
confidence: 99%
“…Chondrocyte hypertrophy in OA may function partly to modulate matrix remodeling and repair (10) and partly to promote calcification, as hypertrophic chondrocytes are commonly co-localized with deposits of hydroxyapatite and calcium pyrophosphate dihydrate crystals in the disease (11). Significantly, deposits of hydroxyapatite and calcium pyrophosphate dihydrate crystals crystals can stimulate intra-articular inflammation and further damage to cartilage in OA (12,13).One of the shared features of hypertrophic chondrocytes in growth plate and articular cartilages is up-regulated expression of two transglutaminase (TG) isoenzymes (14, 15). These are factor XIIIA (FXIIIA), a distinct tissue homodimeric form of the circulating heterotetrameric coagulation factor XIII, and TG2 (also termed tissue TG and G h ), which is unique among the human TG isoenzymes in being a dual function TG and GTPase/ATPase (16).…”
mentioning
confidence: 99%
“…Chondrocyte hypertrophy in OA may function partly to modulate matrix remodeling and repair (10) and partly to promote calcification, as hypertrophic chondrocytes are commonly co-localized with deposits of hydroxyapatite and calcium pyrophosphate dihydrate crystals in the disease (11). Significantly, deposits of hydroxyapatite and calcium pyrophosphate dihydrate crystals crystals can stimulate intra-articular inflammation and further damage to cartilage in OA (12,13).…”
mentioning
confidence: 99%